Investigation of temperature and frequency dependence of electrical conductivity and dielectric behavior in CuS and rGO capped CuS nanocomposites. (28th January 2019) - Ayodhya, Dasari; Veerabhadram, Guttena
Abstract: In this work, we develop a simple and low-cost strategy toward the one-pot synthesis of reduced graphene oxide (rGO) capped copper sulfide (CuS) nanocomposite through an obvious redox transformation reaction between Cu and graphene oxide (GO) without any additive. The prepared CuS and rGO capped CuS nanocomposite have been characterized by various physicochemical techniques for the observation of shape, morphology, and structure. It reveals the average size of the synthesized samples in the range of 10–30 nm with the hexagonal structure. The UV–vis absorption spectra exposed the strong absorption peak of CuS and rGO capped CuS composites in the range of NIR region was observed. The synthesized samples displayed high dielectric constant and electrical conductivity in a wide range of frequency (10 2 –10 6 Hz). The effect of temperature on the electrical conductivity of the synthesized rGO capped CuS nanocomposite was also investigated. The excellent electrical conductivity performance is ascribed to the synergistic effect between CuS and rGO. As the temperature increases, the maximum electrical conductivity of rGO capped CuS composite was exponentially increased at high temperature. The synthesized composite with a high dielectric constant and electrical conductivity is a promising material in high capacitance, and further, it is used as electrode materials for supercapacitors and energy storage applications.